Impact of vehicles passing through the streets of Kokan on the environment. (Experimental technique on CO2 concentration) (Eurasian Research Bulletin, 2022)
This article is aimed at studying the impact of toxic substances emitted from vehicles moving on the streets on the atmosphere. The number and types of vehicles were determined at the intersection of A 373 and A 376 (Turon Street) of the city of Kokan, and experimental results were obtained on the extent to which exhaust gases from the exhaust gases affect the atmosphere and human health.